Calgary family intervention model enhances dietary compliance and knowledge in T2DM patient - Muhtar Muhtar; Aniharyati Aniharyati; Julhana Julhana; Fadlurahmi Fadlurahmi; Muhammad Arifki Zainaro; Martiningsih Martiningsih (Intelektual Pustaka Media Utama, 2026)
The urgency was in developing a more holistic and sustainable approach to supporting type 2 diabetes mellitus (T2DM) patients. This study evaluated the effectiveness of the Calgary Family Intervention Model (CFIM) in improving dietary adherence and knowledge in patients with T2DM. This study used a quantitative method with a quasi-experimental design, involving 280 patients with type 2 diabetes mellitus at the Bolo Community Health Center from January to October 2025. The sample was divided into two groups: intervention (CFIM education) and control (booklet). Data were collected using a valid and reliable questionnaire to measure knowledge and dietary adherence. Data analysis was performed using the Wilcoxon and Mann-Whitney tests. The analysis showed significant results, with the mean knowledge score in the intervention group increasing from 4.84±1.235 to 8.98±2.851 (p < 0.05), while in the control group, it increased from 4.64±1.120 to 7.06±1.219. For dietary adherence, the intervention group showed an increase from 27.00±6.518 to 61.38±7.171 (p = 0.000), compared to the control group, which increased from 27.28±5.592 to 49.44±10.194(p < 0.05). The implications of these results have the potential to strengthen the family-based health intervention model and improve the overall well-being of T2DM patients. This study contributes significantly to family nursing practice by demonstrating the efficacy of the CFIM in enhancing dietary adherence and knowledge among patients with T2DM.